The relevance of reactions of the methyl peroxy radical (CH3O2) and methylhypochlorite (CH3OCl) for Antarctic chlorine activation and ozone loss. Issue 1 (1st January 2018) - Zafar, A. Mannan; Müller, Rolf; Grooss, Jens-Uwe; Robrecht, Sabine; Vogel, Bärbel; Lehmann, Ralph
Abstract: The maintenance of large concentrations of active chlorine in Antarctic spring allows strong chemical ozone destruction to occur. In the lower stratosphere (approximately 16–18 km, 85–55 hPa, 390–430 K) in the core of the polar vortex, high levels of active chlorine are maintained, although rapid gas-phase production of HCl occurs. The maintenance is achieved through HCl null cycles in which the HCl production is balanced by immediate reactivation. The chemistry of the methyl peroxy radical (CH3 O2 ) is essential for these HCl null cycles and thus for Antarctic chlorine and ozone loss chemistry in the lower stratosphere in the core of the polar vortex. The key reaction here is the reactionCH 3 O 2 + ClO → products ; this reaction should not be neglected in simulations of polar ozone loss. Here we investigate the full chemistry of CH3 O2 in box-model simulations representative for the conditions in the core of the polar vortex in the lower stratosphere. These simulations include the reaction CH3 O2  + Cl, the product methylhypochlorite (CH3 OCl) of the reaction CH3 O2  + ClO, and the subsequent chemical decomposition of CH3 OCl. We find that when the formation of CH3 OCl is taken into account, it is important that also the main loss channels for CH3 OCl, namely photolysis and reaction with Cl are considered. Provided that this is the case, there is only a moderate impact of the formation of CH3 OCl in the reaction CH3 O2  + ClO on polar chlorine chemistry in our simulations. Simulated peak mixing ratios of CH3 OCl (≈ 0.25 ppb) occur at the time of the lowest ozone mixing ratios. Further, our model simulations indicate that the reaction CH3 O2  + Cl does not have a strong impact on polar chlorine chemistry. During the period of the lowest ozone concentrations in late September, enhanced values of CH3 O2 are simulated and, as a consequence, also enhanced values of formaldehyde (about 100 ppt) and methanol (about 5 ppt).